The Influence of Organizational Culture and Compensation on Employee Performance Through Employee Job Satisfaction - Nurrachmi Mustafa; Muh. Akob; Edy Jumady (Manunggal Halim Jaya, 2025)
This study examines the influence of organizational culture and compensation on job satisfaction and employee performance among administrative staff at the Faculty of Engineering, Hasanuddin University. Using a quantitative explanatory research design, data were collected from 93 employees through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both organizational culture and compensation have positive and significant effects on job satisfaction. However, organizational culture does not directly affect employee performance; instead, its impact is fully mediated by job satisfaction. Conversely, compensation demonstrates both direct and indirect significant effects on performance. Job satisfaction itself shows a strong positive relationship with employee performance, underscoring its essential role in enhancing work outcomes. These results contribute to the theoretical understanding of human resource management by confirming the mediating role of job satisfaction and emphasizing compensation as a key driver of employee performance. Managerially, the study highlights the need for strengthening cultural values, improving compensation systems, and enhancing non-financial work conditions to foster satisfaction and performance. Despite its contributions, the study is limited by its cross-sectional design, single institutional setting, and reliance on self-reported data. Future research should explore broader institutional contexts and include additional organizational behavior variables to enrich the understanding of performance determinants.